2018
DOI: 10.30631/al-risalah.v14i01.403
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaaan Pemakaian Urf Zakat Emas Perhiasan (Kajian di Selangor dan Malaka)

Abstract: Pembahasan didasarkan pada banyak pendapat Ulama tentang hukum nyata menggunakan emas sebagai perhiasan dari pandangan zakat itu. Fokus dan penekanan akan diberikan untuk melakukan penelitian tentang tingkat bunga tetap urf untuk Malaka dan Selangor pada saat saat ini menjadi. Apa yang paling menarik perhatian adalah zakat pada perhiasan yang berbeda dari jenis lain dari emas karena salah satu harus mereka illah sendiri. Analisis menunjukkan bahwa mayoritas Ulama 'al-Syafi'i termasuk yang diikuti oleh mayoritas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nor Muhammad Faisal bin Md Arifin in a study entitled; "Perbedaaan Pemakaian Urf Zakat Emas Perhiasan (Kajian di Selangor dan Malaka)," It has been very impressive to explain how gold zakat compares in two regions that are relatively different culturally (Arifin, 2018). This research has similarities with the author's study, especially in the context of gold zakat and the method used (comparative study).…”
Section: Literatur Reviewmentioning
confidence: 72%
“…Nor Muhammad Faisal bin Md Arifin in a study entitled; "Perbedaaan Pemakaian Urf Zakat Emas Perhiasan (Kajian di Selangor dan Malaka)," It has been very impressive to explain how gold zakat compares in two regions that are relatively different culturally (Arifin, 2018). This research has similarities with the author's study, especially in the context of gold zakat and the method used (comparative study).…”
Section: Literatur Reviewmentioning
confidence: 72%
“…In terms of zakat on gold and silver, scholars have determined that the nisāb or rate is 2.5%. Studies have indicated that the enforcement of zakat on gold and silver is different based on various customs and practices, and that public awareness on the matter could be better (Md Ariffin, 2014; Sukri, 2016; Ali et al , 2018; Nordin et al , 2018; Nordin et al , 2019). Gold and silver are technically minerals, but other categories of minerals such as diamonds, oil, gas and iron are not subject to zakat.…”
Section: Literature Reviewmentioning
confidence: 99%